2015
DOI: 10.1681/asn.2015030327
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Enhance Male Urinary Tract Infection Severity in a New Model

Abstract: Urinary tract infections (UTIs) occur predominantly in females but also affect substantial male patient populations; indeed, morbidity in complicated UTI is higher in males. Because of technical obstacles, preclinical modeling of UTI in male mice has been limited. We devised a minimally invasive surgical bladder inoculation technique that yields reproducible upper and lower UTI in both male and female mice, enabling studies of sex differences in these infections. Acute uropathogenic Escherichia coli (UPEC) cys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
98
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 69 publications
12
98
0
2
Order By: Relevance
“…Specifically, TNF-␣ was shown to initiate a p38 mitogen-activated protein kinase (MAPK)-dependent "stop signal" that induces neutrophil adhesion and not polarization, resulting in diminished PMN motility toward chemoattractants (38). Existing data indicate that UPEC induces local TNF-␣ secretion during cystitis (21,50), and we show that in the bladder as a whole, TNF-␣ influences early IDO induction in response to UPEC (Fig. 5A).…”
Section: Discussionmentioning
confidence: 64%
“…Specifically, TNF-␣ was shown to initiate a p38 mitogen-activated protein kinase (MAPK)-dependent "stop signal" that induces neutrophil adhesion and not polarization, resulting in diminished PMN motility toward chemoattractants (38). Existing data indicate that UPEC induces local TNF-␣ secretion during cystitis (21,50), and we show that in the bladder as a whole, TNF-␣ influences early IDO induction in response to UPEC (Fig. 5A).…”
Section: Discussionmentioning
confidence: 64%
“…Of note, instillation of uropathogens into the urethra of male mice elicits prostatic infection [111, 112]. In a recently developed, new model of UTI, a small abdominal incision is made and bacteria are inoculated via needle into the bladders of male and female mice, permitting direct sex comparisons [113]. This inoculation method recapitulates the IBC cascade of acute cystitis established in studies with catheter-infected females.…”
Section: Emerging Clinically Relevant Models For Utimentioning
confidence: 99%
“…There are several possible explanations for this finding. Olson et al 12 have demonstrated that male mice are more likely to develop chronic inflammation and persistent bacteriuria after UTI compared with female mice, an association that may be mediated by androgen exposure. In addition, there are several specific etiologies of neurogenic bladder that are only present in boys (eg, posterior urethral valves), or have a male predominance (eg, Eagle-Barrett syndrome).…”
Section: Discussionmentioning
confidence: 99%